The Effect of Subject Lines on Open Rates of Email Marketing Messages - Stupar-Rutenfrans, Snezana; de Koff, Devin; van den Elst, John (Advances in Social Sciences Research Journal, 2019)
This article investigates the effects of email subject lines on the open rate of email marketing messages. Based on previous literature, three different subject lines with distinctive elements of copywriting were developed: a (1) personal, (2) emotion eliciting and (3) short subject line. The open rates of emails with these subject lines were compared to the open rates of emails with a fourth subject line without these copywriting elements, the control group. An A/B test was conducted where an email marketing message sent to a total of 1,409,963 customers of bol.com. Recipients received an email with one out of four possible subject lines. Results show that all emails with subject lines including a distinctive element of copywriting had higher open rates compared to those with a subject line that belonged to the control group. The control group had an open rate of 24.3%, the personal subject line 25.0%, the short subject line 26.9% and the emotion inducing subject line 26.1%. The differences are statistically significant and substantive for bol.com. In conclusion, adjusting a subject line by influencing its content in terms of length, emotional triggers and personalization can all independently lead to a higher open rate of email marketing messages.